THE IMPACT OF MODERN TECHNOLOGIES ON LAW: NEW OBJECTS OF CIVIL LEGAL RELATIONS IN UZBEKISTAN - Shermatov Nuriddin (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study aims to explore the legal frameworks required for governing virtual and digital objects, focusing on the concept of virtual property in gaming and cryptocurrencies. The research examines whether these new forms of property should be regulated within the civil legal system in Uzbekistan. Methods: The research employs a qualitative analysis of case studies and legal precedents, including international examples such as the Ministry of Justice of Taiwan's recognition of virtual property as legal property and the legal implications of in-game theft. Additionally, it evaluates the evolving legal status of virtual tokens and cryptocurrencies across various jurisdictions, integrating a comparative approach to highlight regulatory differences. Results: The findings reveal that while virtual gaming environments are primarily governed by developer-defined rules, real-world legal consequences arise in cases such as hacking or fraud involving virtual property of significant economic value. Furthermore, virtual currencies, including cryptocurrencies and tokens, have gained recognition as property in multiple legal systems despite persistent regulatory challenges. These developments underscore the economic and legal significance of digital assets. Novelty: This study contributes to the emerging field of virtual property law by addressing gaps in legal recognition and proposing a framework for treating digital objects as economic assets deserving of legal protection. It emphasizes the need for civil law systems, particularly in Uzbekistan, to adapt and expand their scope to encompass the unique challenges posed by intangible digital assets. This perspective offers valuable insights for legal scholars and policymakers addressing the implications of digital transformation on civil legal relations.